Agreeing to disagree: The economics of betting exchanges - Karl Whelan (University College Dublin, UCD School of Economics, 2025)
Betting exchanges match people to take opposite sides of a bet. We present a model of a betting exchange in which participants disagree about outcome probabilities but are, on average, correct. Traders maximize subjective expected profits and equilibrium emerges from a simple matching process. The model predicts those who post quotes (Makers) will earn higher returns than those who accept them (Takers) and that loss rates for Takers will rise as the probability of their accepted bet winning falls. Using a large sample of bets on soccer from Betfair Exchange, we implement a transaction-level empirical strategy that identifies Maker and Taker sides of each trade. We show that pre-match and early in-play behavior aligns closely with the model's predictions. However, as matches progress, behavior shifts: longshot bets generate large, systematic losses even for liquidity providers, and profits emerge for those who accept offers on favorites.
Keywords: D83; G14; G41; 330; Betting Exchanges; Bid-Ask Spreads; Betfair; Matching; Thick and Thin Markets